Evaluation of the Learning Program for Physical Education Sports and Health Basic Locomotor Movement Material at State Elementary Schools in Tabir District, Merangin Regency, Jambi - Yogi, Afrisandy Pratama; Arsil, Arsil; Bakhtiar, Syahrial; Syahrastani, Syahrastani (Journal of Physical Education Health and Sport, 2023)
This study aims to evaluate the learning program of Physical Education Sports and Health of basic locomotor movements in Tabir District Public Elementary School, Merangin Regency Jambi, with aspects of the relevance of learning to the merdeka curriculum, the background of physical education sports and health (PJOK) teachers and facilities and infrastructure, the process of implementing Physical Education Sports and Health (PJOK) learning, and the value received during learning. This type of research is qualitative research with a program evaluation method. The design of the research model to be used is based on the CIPP model which involves all parties in the evaluation. Data collection techniques in this study using interviews, documentation, and observation methods. The results of this study from the Context aspect, the PJOK learning program for locomotor basic movement material of State Elementary Schools in Tabir District, Merangin Regency, Jambi is relevant to the Merdeka curriculum that is being implemented in schools. From the Input aspect, public elementary physical education teachers in Tabir District, Merangin Jambi Regency have an undergraduate educational background (S1) in sports education who have completed their education from various universities in Sumatra. From the aspect of facilities and infrastructure in public elementary schools in Tabir District, Merangin Jambi Regency, it is still incomplete. In the process of implementing learning, teachers have used teaching modules and ATP (flow of learning objectives) in accordance with the MERDEKA curriculum but teachers are still learning the curriculum because in some schools there are still teachers who have never attended training related to the merdeka curriculum. From the Product aspect, the achievement of PJOK learning outcomes in the basic locomotor material of State Elementary Schools in Tabir District, Merangin Regency, Jambi has not been maximized. This can be seen from the scores of students who are still below the KKM.